Speckle Noise Suppression Algorithm of Holographic Display Based on Spatial Light Modulator - Li, Nan-Nan; Chen, Chun; Lee, Byoungho; Wang, Di; Wang, Qiong-Hua (Frontiers in Photonics, 2022)
Holography has emerged as one of the most attractive three-dimensional display technologies. With the technological development of computer science and coherent light source, the computer-generated holography has been applied in many fields. However, the speckle noise of the holographic reconstructed image seriously affects the viewing experience. In this paper, the cause of speckle noise generation in holographic display is introduced. Then, discussions about the speckle noise suppression methods are provided. The discussions are categorized into iterative and non-iterative approaches. Besides, we also introduce other speckle noise suppression techniques which are proposed from the perspective of light coherence, human visual system and optical system. Finally, the prospects of different types of approaches are summarized.